2020
DOI: 10.1186/s12889-020-8350-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between parental migration and early childhood nutrition of left-behind children in rural China

Abstract: Background: More than one-third of children under 3 years old are left behind at home due to parental migration in rural China, and we know very little about early childhood nutrition of left-behind children (LBC) because of the dearth of research. This study examined the association between parental migration and early childhood nutrition of LBC in rural China. Methods: We used repeated cross-sectional data of rural children aged 6-35 months who participated in two surveys in six counties of northern and sout… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Several studies have highlighted the psychological problems of caregivers in rural China. In repeated cross-sectional surveys conducted by UNICEF across six counties of northern and southern China, the prevalence of depression in caregivers of rural children aged 6–35 months with non-migrant parents, migrant fathers, and both migrant parents was found to be 40.0, 37.1, and 50.6% in 2013 and 35.9, 31.8, and 38.0% in 2016, respectively [ 4 ]. Previous studies have reported an association between caregivers’ depressive symptoms and social-emotional problems, probably mediated by decreased responsive parenting, lower levels of daily stimulation and acceptance, and other aspects found in poor home environments [ 22 , 31 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have highlighted the psychological problems of caregivers in rural China. In repeated cross-sectional surveys conducted by UNICEF across six counties of northern and southern China, the prevalence of depression in caregivers of rural children aged 6–35 months with non-migrant parents, migrant fathers, and both migrant parents was found to be 40.0, 37.1, and 50.6% in 2013 and 35.9, 31.8, and 38.0% in 2016, respectively [ 4 ]. Previous studies have reported an association between caregivers’ depressive symptoms and social-emotional problems, probably mediated by decreased responsive parenting, lower levels of daily stimulation and acceptance, and other aspects found in poor home environments [ 22 , 31 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of left-behind children in rural settings is 40% in South Africa, 36% in Ecuador, and 27% in the Philippines [ 2 ]. The previous literature has revealed high risks of poor nutrition, well-being, and mental health among left-behind children [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Tedeschi and Calhoun [11], the PTG experience is significantly reliant on how stressful a situation is rated. Even though various researchers have reported positive [32,33], negative [34,35], or null [36,37] associations between stress and PTG, the nature and directionality of this link in a sample of left-behind children remain poorly understood. Accordingly, this study formulated the following hypothesis: Hypothesis 1.…”
Section: Perceived Stress and Post-stress Growthmentioning
confidence: 99%
“…In our sample, the majority of primary caregivers are female (most likely mothers or grandmothers), which is another similarity to other samples in rural China. Previous studies in rural China have demonstrated high quantities of left-behind children and female caregivers, who are financially supported by caregivers who migrate away from home to find work outside the household [ 50 52 ]. Thus, many female primary caregivers in rural China are solely responsible for looking after children and managing household affairs [ 53 ], while other household members work outside the home to financially support the family [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%